Pengembangan Diri Mahasiswa Institut Shanti Bhuana Dalam Berwirausaha - Sabinus Beni sabinus (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this study is to analyze data on student self-development which can develop and help them to train mental resilience so that they can develop into better individuals. Because like it or not, they must be trained to have the character of fighters and leaders. Entrepreneurship means opening a personal business which can later be transferred to other people. If one day they are tired of running a business, the business they have pioneered for years can be passed on to those closest to them, for example to their children or spouse. It is different if they work for other people. The benefits they get from the company are only in the form of pension guarantees. Of course, there is nothing they can pass on to their offspring, and this is also to start a business from scratch is not easy. It takes a character who is resilient and doesn't give up. Entrepreneurship helps they train mental toughness. them, and they can also develop into better individuals. Because like it or not they must be trained to have warrior and leader characters, and there is no term i hate my job, it is impossible for someone to start a personal business in a field that they do not like. choosing his own line of business makes him love his job. This freedom to choose is not owned by office workers, therefore, they often feel compelled to carry out their work.